Problem Solving Strategies used by Pre-service Teachers in Learning Technology - Gopal, Pranita (JOURNAL OF INDIAN EDUCATION, 2014)
Using technology in the classroom to augment the learning of the students is becoming a professional responsibility of teachers in today’s technology infused world. Teachers have to constantly learn new software. Learning new software is akin to solving an ill-structured problem and it requires the use of various problem solving skills used either in tandem or individually. The present study is an interpretive qualitative study of eight pre-service teachers, narrowed down from 99 pre-service teachers who participated in this study. The study discusses the problem solving processes used by these pre-service teachers while learning how to use Hot Potatoes™ to create an Online Question Bank in their discipline. Implications of working in such a technology enabled problem solving environment are also discussed.